2014
DOI: 10.3109/17435390.2014.902519
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of carbon nanotube variants: A comparativein vitroexposure study with A549 epithelial and J774 macrophage cells

Abstract: While production of engineered carbon nanotubes (CNTs) has escalated in recent years, knowledge of risk associated with exposure to these materials remains unclear. We report on the cytotoxicity of four CNT variants in human lung epithelial cells (A549) and murine macrophages (J774). Morphology, metal content, aggregation/agglomeration state, pore volume, surface area and modifications were determined for the pristine and oxidized single-walled (SW) and multi-walled (MW) CNTs. Cytotoxicity was evaluated by cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 44 publications
4
53
1
Order By: Relevance
“…Bottini et al 65 found that MWCNTs oxidized by concentrated HNO 3 exhibited a stronger cytotoxic effect to human T lymphocytes than fresh MWCNTs. Kumarathasan et al 8,9 also observed an increase in cytotoxicity (A549 and J774 cells) for CNTs oxidized by a 3:1 (v/v) mixture of H 2 SO 4 /HNO 3 . In those studies, the increase in toxicity was attributed to surface modification (carboxylic acids) which resulted in a transformation from hydrophobic to hydrophilic CNTs.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Bottini et al 65 found that MWCNTs oxidized by concentrated HNO 3 exhibited a stronger cytotoxic effect to human T lymphocytes than fresh MWCNTs. Kumarathasan et al 8,9 also observed an increase in cytotoxicity (A549 and J774 cells) for CNTs oxidized by a 3:1 (v/v) mixture of H 2 SO 4 /HNO 3 . In those studies, the increase in toxicity was attributed to surface modification (carboxylic acids) which resulted in a transformation from hydrophobic to hydrophilic CNTs.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Detailed descriptions of these assays are given elsewhere. 8,9 Functional Group Characterization of SWCNT. Functional groups were characterized before and after oxidant/ambient air exposures by Fourier transform infrared (FTIR) spectroscopy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The total acidity of the surface of SiNPs was quantified following the acid-base titration procedure reported earlier (Eitan et al, 2003;Kumarathasan et al, 2015).…”
Section: Quantitation Of Surface Aciditymentioning
confidence: 99%
“…The cytotoxicity of SiNPs was assessed using the integrated bioassay which enabled the analysis of the redox state (resazurin reduction), energy metabolism (cellular ATP) and cell membrane integrity (LDH release) and was conducted as previously described (Kumarathasan et al 2015). Cell proliferation was assessed separately, using the BrdU incorporation assay.…”
Section: Sequence Of Assaysmentioning
confidence: 99%
“…The cells (50 µl) were transferred to an opaque white plate (Beyotime Institute of Biotechnology) at 24, 48 and 72 h. The fluorescence value was tested using a fluorescence luminometer (F97Pro; Shanghai Lengguang Technology Co. Ltd, Shanghai, China). Relative proliferative activity = appreciation rate of fluorescence value of treatment group / appreciation rate of fluorescence value of control group (28). qPCR assay.…”
Section: Methodsmentioning
confidence: 99%